2015
DOI: 10.5539/elt.v9n1p65
|View full text |Cite
|
Sign up to set email alerts
|

Just-In-Time Teaching Techniques through Web Technologies for Vocational Students’ Reading and Writing Abilities

Abstract: This research compares the English language achievements of vocational students, their reading and writing abilities, and their attitudes towards learning English taught with just-in-time teaching techniques through web technologies and conventional methods. The experimental and control groups were formed, a randomized true control group pre-test-post-test design was used, and the data were analyzed by t-tests for dependent and independent samples. The study's results showed significant differences in English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…As regards language learning, JiTT is said to be effective in addressing the constraints of EFL contexts (Lee & Wallace, 2018). Typically, language learners positively value the shift from a traditional lecture-based lesson to a more student-centred and autonomous learning method (Campillo-Ferrer & Miralles-Martínez, 2021), and this change in the teaching approach tends to lead to better attitudes towards English learning (Chantoem & Rattanavich, 2016). Moreover, JiTT has proven effective in improving learners' speaking (Teng, 2018) and writing (Chantoem & Rattanavich, 2016) skills, and satisfaction with the goals achieved in language courses has also been enhanced when students have followed the JiTT approach (Hung, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards language learning, JiTT is said to be effective in addressing the constraints of EFL contexts (Lee & Wallace, 2018). Typically, language learners positively value the shift from a traditional lecture-based lesson to a more student-centred and autonomous learning method (Campillo-Ferrer & Miralles-Martínez, 2021), and this change in the teaching approach tends to lead to better attitudes towards English learning (Chantoem & Rattanavich, 2016). Moreover, JiTT has proven effective in improving learners' speaking (Teng, 2018) and writing (Chantoem & Rattanavich, 2016) skills, and satisfaction with the goals achieved in language courses has also been enhanced when students have followed the JiTT approach (Hung, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Typically, language learners positively value the shift from a traditional lecture-based lesson to a more student-centred and autonomous learning method (Campillo-Ferrer & Miralles-Martínez, 2021), and this change in the teaching approach tends to lead to better attitudes towards English learning (Chantoem & Rattanavich, 2016). Moreover, JiTT has proven effective in improving learners' speaking (Teng, 2018) and writing (Chantoem & Rattanavich, 2016) skills, and satisfaction with the goals achieved in language courses has also been enhanced when students have followed the JiTT approach (Hung, 2017). Indeed, Colomo-Magaña et al (2020) surveyed 123 trainee teachers and concluded that the application of JiTT fostered the development of oral skills and the improvement of learning abilities, which could be linked to the fact that JiTT may lower learners' anxiety when speaking in the FL (Edwards & Murphey, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, due to their concerns over grammar, most Thai vocational students seek to learn English but do not use it frequently in daily life. In addition, students have minimal time outside of class to practice English [16]. In addition, Ratnaningsih and Azizah [17] found that most students at a State Vocational High School in Jakarta were unaware of the errors in their writing and did not always know the appropriate word choice for constructing their sentences.…”
Section: Introductionmentioning
confidence: 99%
“…As technology continues to advance, a new way of teaching is also arising, "visualization" or visual learning became essential in today's education [7]. Another teaching method is the use of "writing and reading" as alternative techniques to improve students' performance in class [8].…”
Section: Introductionmentioning
confidence: 99%